Evaluation of Alum/Lime Coagulant for the Removal of Turbidity from Al- Ahdab Iraqi Oilfields Produced Water (Journal of Engineering, 2015)
The removal of turbidity from produced water by chemical coagulation/flocculation method using locally available coagulants was investigated. Aluminum sulfate (alum) is selected as a primary coagulant, while calcium hydroxide (lime) is used as a coagulant aid. The performance of these coagulants was studied through jar test by comparing turbidity removal at different coagulant/ coagulants aid ratio, coagulant dose, water pH, and sedimentation time. In addition, an attempt has been made to examine the relationship between turbidity (NTU) and total suspended solids (mg/L) on the same samples of produced water. The best conditions for turbidity removal can be obtained at 75% alum+25% lime coagulant at coagulant dose of 80 mg/l at pH 6 and 120 min for sedimentation time. At these conditions, the turbidity reading was reduced from 92 to 2.1 NTU.